Tidal stream generators, current state and potential opportunities for condition monitoring - Kappatos, Vassilios; Georgoulas, George; Avdelidis, Nicolas Peter; Salonitis, Konstantinos (JVE International, 2016)
Tidal power industry has made significant progress towards commercialization over the past decade. Significant investments from sector leaders, strong technical progress and positive media coverage have established the credibility of this specific renewable energy source. However, its progress is being retarded by operation and maintenance problems, which results in very low operational availability times, as low as 25 %. This paper presents a literature review of the current state of tidal device operators as well as some commercial tidal turbine condition monitoring solutions. Furthermore, an overview is given of the global tidal activity status (tidal energy market size and geography), the key industry activity and the regulations-standards related with tidal energy industry. Therefore, the main goal of this paper is to provide a bird’s view of the current status of the tidal power industry to serve as a roadmap for the academia regarding the real needs of the tidal power industry.
Keywords: Tidal stream generators; tidal power; condition monitoring; literature review